Minimally Invasive Surgery in Childhood Cancer: A Challenging Future - Peycelon, Matthieu; Audry, Georges; Irtan, Sabine (European Journal of Pediatric Surgery, 2014)
Introduction Minimally invasive surgery (MIS) has emerged as an alternative to open approach for cancer diagnosis in children ∼20 years ago, but only recently for tumor resection. The purpose of this review is to update the use of MIS in pediatric oncological surgery over the past five years.Methods The authors conducted a systematic review of papers published between 2009 and 2014 focusing on indications and results of the technique.Results New indications in Wilms tumor, pheochromocytoma, and lung nodules have emerged, thanks to the growing use of MIS in benign urological and thoracic surgery with satisfactory results. Case control studies comparing MIS to open approach have been published for the first time in more classical indications such as neurogenic tumors, while robot-assisted procedure has shown concern in results about its early experience in solid tumors.Conclusion MIS is a promising method for removal of thoracic and abdominal malignancies as long as oncological principles are strictly followed. Long-term follow-up is mandatory to further delineate objective indications.
Keywords: minimally invasive surgery; pediatric oncology; pediatric surgery